Identificación y fluctuación poblacional de insectos Polinizadores en Sacha Inchi (Plukenetia Volubilis l.) (Euphorbiaceae) - Rojas Perez, Ronald (2011)
The essay is entitled "Identification and population fluctuation of insects pollinators in growing Sacha Inchi (Plukenetia volubilis L.); with the aim of identifying the different species of pollinating insects in the crop. Also evaluate the fluctuations of insect populations in relation to temperature, the present study was conducted in the experimental fields of the Peruvian Amazon Research Institute (IIAP) located in the village of Bello Horizonte in the District Banda de shilcayo Province of San Martin, which is to 7 km from Tarapoto's city. The investigation had a duration 03 months approximately of September to November, 2010. The statistical system used was nonparametric. The results demonstrated that Apis mellifera and polybia occidentalis were the populations insectiles that were visited pistillate inflorescences which are considered to be pollinators of this crop sacha inchi (Plukenetia volubilis L). And other species such as Polybia sp, sp Amenia, Acromirmex sp sp Nannotrigona and Tetragonisca angustula are considered visitors to the inflorescences staminate flower. The anthesis is diurnal, opening between 5:00 a.m. to 5:30 a.m. remained so for 35 to 48 hours. The duration of flowering in inflorescence could be considered too long to take 46.65 days in average. The development of staminate flower button and reaches 26.81 days. Finally, the cross-pollination (outcrossing) is the predominant breeding system in this crop.